2021
DOI: 10.25181/jppt.v21i3.2133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Priming on Vigor of Germinated Chili (Capsicum annum L.) Seeds in Aluminium Stress Conditions

Abstract: Seed germination in ultisol is a problem. Ultisol has a low pH, poor in nutrients and organic matter, and high Al content. The low physiological quality of seeds is also a limiting factor. The purpose of this study was to determine the effect of priming on the seed vigor of two chili varieties whose seeds have expired and have not expired. This experiment consisted of 2 experiments, namely Experiment 1, which used seeds that had expired (deteriorating), and Experiment II, which used seeds that had not expired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…Moreover, [10] and [25] stated that triggering the metabolic process through seed drying and hydration prior to germination due to priming treatment could increase the percentage and rate of germination, and improve seedling growth either under normal or under various abiotic stresses. The results were also consistent with earlier studies that found that hydro, osmo, or hormone priming improved seed germination in stored okra seeds [26], and chili [28,29]. [4] further stated that invigoration strategies such as hydro priming, osmo conditioning, and hormonal priming were able to shorten the emergence time of stored seeds in various horticultural crops.…”
Section: Germination Percentage Germination Time Shoot Length and Roo...supporting
confidence: 91%
“…Moreover, [10] and [25] stated that triggering the metabolic process through seed drying and hydration prior to germination due to priming treatment could increase the percentage and rate of germination, and improve seedling growth either under normal or under various abiotic stresses. The results were also consistent with earlier studies that found that hydro, osmo, or hormone priming improved seed germination in stored okra seeds [26], and chili [28,29]. [4] further stated that invigoration strategies such as hydro priming, osmo conditioning, and hormonal priming were able to shorten the emergence time of stored seeds in various horticultural crops.…”
Section: Germination Percentage Germination Time Shoot Length and Roo...supporting
confidence: 91%
“…Remarks: KN1 = Normal number of sprouts on the first count on the 7th day 6. Electric Conductivity is measured in the following way, after a quick depreciation treatment, the seeds are weighed, then put into a cup containing 25 aquadest noodles and covered with aluminum foil, after being left for 6 hours at a temperature of around 10°C (Agustiansyah et al, 2021). The seeds are filtered and the aguabides from soaking the seeds are measured DHL.…”
Section: Chili Seed Vigor Testing Methodsmentioning
confidence: 99%
“…Pada proses invigorasi yang panjang terjadi peningkatan mutu terhadap kecepatan tumbuh, keserempakan perkecambahan, serta pengurangan tekanan lingkungan yang suboptimal selama proses invigorasi. Agustiansyah et al, (2021) menyampaikan perlakuan benih kedaluarsa menggunakan teknik perendaman dan penambahan fitohormon dapat meningkatkan daya berkecambah. Benih kedaluarsa yang dikecambahkan tanpa penambahan zat pengatur tumbuh atau zat kimia lainnya akan menghasilkan nilai berkecambah yang relatif rendah karena viabilitas dan vigor benih menurun.…”
Section: Abstrakunclassified